Visualisasi Karya Patchwork Sebagai Usaha Penyadaran Menjaga Kelestarian Lingkungan - Centaury Harjani (Institut Seni Indonesia Yogyakarta, 2016)
The work of art has a lot of variety, concepts, themes, until the destination in the making art. The sameness in every work of art that each work must have had the mark or the symbolism that will be showed through the work. This paper contains the elaboration of a work textile craft